Xylene-1, 4-bis[4-(p-pyrrolidinostyryl)benzothiazolium borate] salt as new functional dye. (March 2015) - Kabatc, Janina; Jurek, Katarzyna; Czech, Zbigniew; Kowalczyk, Agnieszka
Abstract: New dye, xylene-1, 4-bis[4-( p -pyrrolidinostyryl)benzothiazolium bromide] has been synthesized and its spectroscopic, electrochemical properties, and application as a photosensitizer in polymer chemisrty were investigated. The photoinitiating ability of new photoinitiator was compared with photoinitiating efficiency of mono-cationic analog.